Sleep quality and subjective well-being in healthcare students: examining the role of anxiety and depression - Zhu, Yihong; Meng, Runtang; Jiang, Chen; Yang, Nongnong; Huang, Mengyi; Wang, Xiaowen; Zou, Wenjing; Lou, Chen; Xiao, Ruohan; Lu, Jingjing; Xu, Jiale; Jiménez-Correa, Ulises; et al. (Frontiers in Public Health, 2023)
Objective: Sleep issues, negative emotions, and health conditions are commonly co-occurring, whereas their associations among healthcare students have yet to be elucidated. This study aimed to examine whether anxiety and depression mediate the relationship between sleep quality and subjective well-being in healthcare students.A cross-sectional survey was conducted among Chinese healthcare students (N = 348). A battery of paper-and-pencil questionnaires-the Chinese version of the Sleep Quality Questionnaire (SQQ), the World Health Organization-Five Well-Being Index (WHO-5), and the Patient Health Questionnaire-4 (PHQ-4) were applied. Descriptive analysis with means (standard deviations) and counts (proportions), Spearman correlation analysis between the SQQ, the WHO-5, and the PHQ-4, and mediation analysis via structural equation models were performed.Results: Correlational analysis revealed statistically significant associations between sleep quality, anxiety and depression, and well-being among healthcare students. Mediation analysis identified that poor sleep quality produced relatively low levels of self-reported well-being, which were entirely attributable to anxiety and depression.Conclusions: Sleep quality was associated with subjective well-being, and this interrelationship was fully mediated by anxiety and depression. Interventions aimed at promting sleep quality of healthcare students may contribute to promoting their well-being by reducing anxiety and depression.